Removal of Refractory Organics from Biologically Treated Landfill Leachate by Microwave Discharge Electrodeless Lamp Assisted Fenton Process - Jiuyi Li; Lele Qin; Lei Zhao; Aimin Wang; Yong Chen; Liao Meng; Zhongguo Zhang; Xiujun Tian; Yanmei Zhou (International Journal of Photoenergy)
Biologically treated leachate usually contains considerable amount of refractory organics and trace concentrations of xenobiotic pollutants. Removal of refractory organics from biologically treated landfill leachate by a novel microwave discharge electrodeless lamp (MDEL) assisted Fenton process was investigated in the present study in comparison to conventional Fenton and ultraviolet Fenton processes. Conventional Fenton and ultraviolet Fenton processes could substantially remove up to 70% of the refractory organics in a membrane bioreactor treated leachate. MDEL assisted Fenton process achieved excellent removal performance of the refractory components, and the effluent chemical oxygen demand concentration was lower than 100 mg L−1. Most organic matters were transformed into smaller compounds with molecular weights less than 1000 Da. Ten different polycyclic aromatic hydrocarbons were detected in the biologically treated leachate, most of which were effectively removed by MDEL-Fenton treatment. MDEL-Fenton process provides powerful capability in degradation of refractory and xenobiotic organic pollutants in landfill leachate and could be adopted as a single-stage polishing process for biologically treated landfill leachate to meet the stringent discharge limit.